A Review On Implementing Knowledge Management In Healthcare - Suzan Katamoura, Mehmet Sabih Aksoy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Healthcare is a dynamic profession that is continuously changing and evolving. Doctors are always in circumstances where they have to think, analyze and process a wide range of medical conditions, laboratory and radiology results, medications, treatment history, and similar patients' cases to make decisions. Therefore, healthcare is a knowledge-driven field. Thus, implementing healthcare knowledge management systems will support streamlining information to achieve the most efficient patient care. In addition, a proper knowledge management system will assist stakeholders in policy development and decision making by maintaining the information flow between the stakeholders and staff, which will result in higher productivity. This paper offers an overview of knowledge management implementations in healthcare organizations, including the types of healthcare knowledge, the importance of knowledge management for healthcare, and the advantages and disadvantages of implementing these systems. The work also introduces several relevant concepts related to this field, such as big data and expert systems